2010
DOI: 10.2527/jas.2009-2593
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an appropriate mode of comparison for measuring the performance of marbling score output from video image analysis beef carcass grading systems1,2

Abstract: A beef carcass instrument grading system that improves accuracy and consistency of marbling score (MS) evaluation would have the potential to advance value-based marketing efforts and reduce disparity in quality grading among USDA graders, shifts, and plants. The objectives of this study were to use output data from the Video Image Analysis-Computer Vision System (VIA-CVS, Research Management Systems Inc., Fort Collins, CO) to develop an appropriate method by which performance of video image analysis MS output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 10 publications
(15 reference statements)
2
15
0
1
Order By: Relevance
“…Strong, positive correlations (P < 0.0001) were observed between marbling score and fat percentage for each method: CEM (r = 0.91), ether (r = 0.93), and Folch (r = 0.90; data not presented in tabular form). Similar correlations were also observed in previous research (McBee and Wiles, 1967;Armbruster et al, 1983;Moore et al, 2010).…”
Section: Crude Fatsupporting
confidence: 92%
See 4 more Smart Citations
“…Strong, positive correlations (P < 0.0001) were observed between marbling score and fat percentage for each method: CEM (r = 0.91), ether (r = 0.93), and Folch (r = 0.90; data not presented in tabular form). Similar correlations were also observed in previous research (McBee and Wiles, 1967;Armbruster et al, 1983;Moore et al, 2010).…”
Section: Crude Fatsupporting
confidence: 92%
“…Fat percentage increased as marbling score increased (P < 0.05) regardless of fat extraction method (Table 4). These results agree with previous research where ether was used and indicated that fat percentage increased with an increase in marbling scores (McBee and Wiles, 1967;Savell et al, 1986;Moore et al, 2010). Strong, positive correlations (P < 0.0001) were observed between marbling score and fat percentage for each method: CEM (r = 0.91), ether (r = 0.93), and Folch (r = 0.90; data not presented in tabular form).…”
Section: Crude Fatsupporting
confidence: 91%
See 3 more Smart Citations